Dendrimer-based nanoparticles for potential personalized therapy in chronic lymphocytic leukemia: Targeting the BCR-signaling pathway - Franiak-Pietryga, Ida; Maciejewski, Henryk; Ostrowska, Kinga; Appelhans, Dietmar; Voit, Brigitte; Misiewicz, Malgorzata; Kowalczyk, Pawel; Bryszewska, Maria; Borowiec, Maciej (International Journal of Biological Macromolecules, 2016)
Chronic lymphocytic leukemia (CLL) is one of the most prevalent forms of leukemia in western society. Although classic chemoimmune therapy is still the gold standard of care for leukemic patients, effective therapy of CLL is yet to be achieved. The present study examines the influence of poly(propylene)imine (PPI) dendrimers with primary amino surface groups modified with maltotriose residues in approximately 90% (PPI-G4-DS-Mal-III) or 30% (PPI-G4-OS-Mal-III) of cases on CLL cells (MEC-1 cell line with del(17p)), and confirms that the main trigger in this interaction is the induction of the apoptotic mechanism. The efficacy of each dendrimer was compared using fludarabine (FA). Gene expression profiling (GEP) by microarray identified a group of genes in the BCR signaling pathway characterized by different levels of expression directly associated with the tested agent and type of interaction. Network analysis revealed the potential patterns involved in potential personalized therapy of CLL. The expression of most BCR genes decreased under the influence of dendrimers, which might translate into decreased maturation and proliferation of CLL lymphocytes. Moreover, PPI-G4-OS/DS-Mal-III dendrimers affected gene expression and CLL cells in a different way to FA. Thanks to unique properties, dendrimers may be specifically targeted, thus improving the effectiveness of CLL therapy.
CRIS-Team Scopus Importer:2023-03-20
Keywords: B-cell receptor (BCR); Chronic lymphocytic leukemia (CLL); Gene expression; Poly(propylene imine)dendrimers (PPI)